2020
DOI: 10.3390/rs12213558
|View full text |Cite
|
Sign up to set email alerts
|

Mining and Restoration Monitoring of Rare Earth Element (REE) Exploitation by New Remote Sensing Indicators in Southern Jiangxi, China

Abstract: Rare earth elements (REEs) are widely used in various industries. The open-pit mining and chemical extraction of REEs in the weathered crust in southern Jiangxi, China, since the 1970s have provoked severe damages to the environment. After 2010, different restorations have been implemented by various enterprises, which seem to have a spatial variability in both management techniques and efficiency from one mine to another. A number of vegetation indices, e.g., normalized difference vegetation index (NDVI), soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 68 publications
0
17
0
1
Order By: Relevance
“…The dryland-tailored vegetation index, GDVI, is shown in Equation (1). When n = 1, GDVI = NDVI; when n = 2, it is suitable for characterizing dryland biomes including shrubland, woodland and forest; when n = 3, it can be used for monitoring the degradation and desertification in sparsely vegetated area [22,23]. Compared with NDVI and other vegetation indices, GDVI has higher sensitivity and dynamic range, and is able to identify more effectively subtle differences in vegetation greenness in low vegetated areas [22].…”
Section: Processing Procedures Satellite Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…The dryland-tailored vegetation index, GDVI, is shown in Equation (1). When n = 1, GDVI = NDVI; when n = 2, it is suitable for characterizing dryland biomes including shrubland, woodland and forest; when n = 3, it can be used for monitoring the degradation and desertification in sparsely vegetated area [22,23]. Compared with NDVI and other vegetation indices, GDVI has higher sensitivity and dynamic range, and is able to identify more effectively subtle differences in vegetation greenness in low vegetated areas [22].…”
Section: Processing Procedures Satellite Data Processingmentioning
confidence: 99%
“…However, it is difficult to discern subtle changes in vegetation when applied to desert areas with sparse vegetation. Recently, Wu (2014) proposed the generalized difference vegetation index (GDVI) for arid areas [22], and Xie et al (2020) developed a set of monitoring and restoration assessment indicators (MRAIs) for assessing the mining impacts and restoration effectiveness [23]. Since these two indicators were developed for sparse vegetation areas, both of them are promising for land degradation and desertification study.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the actual land cover characteristics of Hefei, three types of vegetation indices were selected, namely NDVI, EVI and GDVI (n = 2) (Wu, 2014;Xie et al, 2020), the formulae for the three types of vegetation index are shown as follows:…”
Section: Processing Proceduresmentioning
confidence: 99%
“…Sensors 2022, 22,1948 2 of 22 Also, Felipe de Lucia Lobo et al graphed the landscape of a mining area in Amazon, Brazil, based on multispectral data obtained from supervised classification with a kappa coefficient of 0.7 [8]. Using Landsat multispectral data, Lifeng Xie et al extracted multiple ecological index and established mining and restoration assessment indicators (MRAIs), which are applicable in data collection and supervision of restoration in mining areas of southern JiangXi province, China [9]. Li Hengkai et al applied Sentinel-2 images to research the devastation and restoration of rare earths regions [10].…”
Section: Introductionmentioning
confidence: 99%